Modification of Regenerated Cellulose Membranes with Cationic Polymer and Its Cr(Vi) Retention Capacity - Sanchez-Poblete, J; Tapiero-Martinez, y (Elsevier Ltd, 2019)
In this work, we report the modification of regenerated cellulose membranes through the “in situ” polymerization of [2-(acryloyloxy)ethyl] trimethylammonium chloride monomer and N,N -methylenebis(acrylamide) crosslinker. The polymerization reaction was performed using 1% mol of ammonium persulfate as initiator, and varying both the monomer concentration (10–25 mmol/L) and the percentage of crosslinker (4 and 8 mol%). The degree of modification (DM) and water absorption capacity (WAC) at different pHs were calculated gravimetrically. These modified membranes were characterized by FTIR, SEM, TGA, electrokinetic potential and permeability. The Cr(VI) retention capacity of the modified membranes was evaluated at different pHs. The DM values were between 23.46% and 41.82%. The highest WAC was for the membrane prepared with 25 mmol/L of monomer and 4 mol% of crosslinker independent of the pH value. The FTIR characterization showed absorption bands confirming this membrane modification. The SEM analysis showed the morphological changes of the membranes by the presence of interpolymeric networks. TGA showed a typical thermogravimetric curve of the polymers that contain quaternary ammonium groups. Modified ultrafiltration membranes exhibited good thermal stability. Electrokinetic potential revealed that the modified membrane is cationic in a wide range of pH and permeability test showed that all the modified membranes decrease the volumetric flux. The results of Cr(VI) retention indicate that it is possible to remove this metal at different pHs (3, 6 and 9), highlighting the highest retention at pH 6, reaching a value of 94% when 20 mg/L of chromium (VI) was used in the feed. © 2018 Elsevier Ltd